The Effect of 4-weeks Rehabilitation Program on Range of Motion and - Sajjad Rowshani; Afshin Moghaddasi; Maryam Abbasi; Amir Abdol-Mohammadi; Shahram Ahanjan (Sālmand, 2010)
Objectives: The purpose of this study was to investigate the effect of 4-weeks rehabilitation, electrotherapy and kinesiotherapy programs on range of motion shoulder pain in men with idiopathic frozen shoulder.